2020
DOI: 10.1097/txd.0000000000001053
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sarcopenia on Simultaneous Pancreas and Kidney Transplantation Outcomes: A Retrospective Observational Cohort Study

Abstract: Background. Sarcopenia has been identified as a predictive variable for surgical outcomes. We hypothesized that sarcopenia could be a key measure to identify frail patients and potentially predict poorer outcomes among recipients of simultaneous pancreas and kidney (SPK) transplants. Methods. We estimated sarcopenia by measuring psoas muscle mass index (PMI). PMI was assessed on perioperative computed tomography (CT) scans of SPK recipients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Streja et al used low serum creatinine as a surrogate for low muscle mass in a large registry data analysis and concluded that low muscle mass tends to result in poorer graft survival [ 29 ]. Interestingly, in a study of a patient collective that had received simultaneous pancreas-kidney transplantation, significantly lower pancreas survival, but not kidney survival, was seen in sarcopenic patients [ 30 ]. In our work, we showed that, in addition to sarcopenia, donor age and use of organs from deceased donors were associated with poorer transplant function in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streja et al used low serum creatinine as a surrogate for low muscle mass in a large registry data analysis and concluded that low muscle mass tends to result in poorer graft survival [ 29 ]. Interestingly, in a study of a patient collective that had received simultaneous pancreas-kidney transplantation, significantly lower pancreas survival, but not kidney survival, was seen in sarcopenic patients [ 30 ]. In our work, we showed that, in addition to sarcopenia, donor age and use of organs from deceased donors were associated with poorer transplant function in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…While there are only a few publications dealing with sarcopenia as a predictor of kidney graft outcome [5,16,19,20,30,31], a large number of studies published in the last years show an increased postoperative morbidity and mortality after visceral surgery and in oncologic patients [37][38][39][40][41][42][43]. A meta-analysis explored independent risk factors for [45].…”
Section: Discussionmentioning
confidence: 99%
“…Independent of recipient age, recent studies have focused on the impact of sarcopenia and functional status on outcomes following SPKT. [59][60][61] DM is believed to contribute directly to the pathophysiology of frailty by increasing the risk of sarcopenia. Patients with T1DM in particular are at greater risk for sarcopenia secondary to the catabolic effect of insulin deficiency and excess accumulation of intramyocellular lipids and advanced glycation end products.…”
Section: Afaneh Et Al Reported On 136 Consecutive Pancreas Transplants 17mentioning
confidence: 99%
“…In contrast, kidney graft survival, patient survival, surgical complications, hospital stay, delayed kidney graft function, infections, and readmissions were not influenced by PMI. 92 In contrast to the few studies in pancreas transplantation, there are multiple studies evaluating the effect of frailty on pretransplant and peritransplant outcomes among various other solid organ transplant recipients, mainly in kidney transplantation. It is estimated that approximately 20% of ESRD patients listed for a kidney transplant are frail.…”
Section: Pretransplant Frailty Assessment and Riskmentioning
confidence: 99%
“…96 However, the rate of acute rejections was not significantly different in patients with lower PMI compared with those with normal PMI in that study, nor were there differences in surgical complications, infections, or patient deaths, probably indicating the study was inadequately powered due to the small sample size and varied transplant types. 94 Recently, Meier et al 92 studied 107 SPK recipients who had computed tomography scans in the perioperative period and found that patients with a low PMI were 6 times more likely to lose their pancreas allograft. In contrast, kidney graft survival, patient survival, surgical complications, hospital stay, delayed kidney graft function, infections, and readmissions were not influenced by PMI.…”
Section: Introductionmentioning
confidence: 99%